Clinical profile of human immunodeficiency virus infection in children: an interesting prospective study - Deshmukh, Sunil B.; Mogre, Sandeep; More, S. S.; Deshmukh, Khushbu S. (International Journal of Contemporary Pediatrics, 2016)
Background: HIV infection has become a pandemic affecting both industrialized & developing countries. The increase in pediatric HIV infection has had a substantial impact on childhood mortality both in industrialized countries and developing countries. It is believed that this study will motivate research worker to work for further improvement of the disease, clinical presentation, diagnostic measures and management in already existing health care delivery system in a tertiary care centre in the tribal area and which may lead to even better survival and quality of life for these children. With the above background, the study is taken up to find the clinical profile of HIV infection in pediatric population in the study area. Methods: The current hospital based prospective study was carried out in the department of pediatrics, Shri V. N. Government Medical College, Yavatmal (Maharashtra), India from 1st January 2011 to 30th June 2012. 108 cases of HIV attending the pediatric OPD and IPD were included in the study. Importance of test was explained to the parents. HIV was diagnosed by using Standard Protocol. All those who were positive by ELISA, confirmed it by repeat test after 3 months. Western blot was not possible due to non availability of kits. Confirmations of all infections were done as per strategies suggested by WHO. Due to non-availability of specific but expensive test like PCR, p24 antigen assay or HIV Culture, children of PPTCT positive mother were tested on follow up after 18 month age to determine whether the transmission was vertical. Results: Majority (60.18%) cases in this study are below 5 years of age. Maximum cases 33(30.55%) were between 5-10yrs of age and 5 cases (4.62%) were below 18 months. Males 69(63.88%) outnumbered females 39(36.11%) with M: F ratio of 1.76:1. In the present study predominant route of transmission of HIV to the child was by perinatal (vertical) transmission (98.15%). Maximum 64(59.25%) were home delivered cases followed by 29(26.85%) normal hospital delivered and 6(5.55%) LSCS/instrumental delivered cases. In present study 60(55.55%) severe malnutrition (Group III and IV) was the most common examination finding. Of the total 108 cases enrolled in the study, 75 cases had regular follow up for 250 times and 33 cases did not follow up. Majority of follow ups were for respiratory complaints (23.20%) and fever (17.60%). Only 7.20% patients came for follow up were asymptomatic. Most of the follow up were for OI’s. In this study, 108 cases of the study group visited 250 times in our hospital. Out of these 90 cases had 212 episodes of OI’s and 18 cases had no evidence of OI’s. Conclusions: HIV infection is an unpredictable disease in infants, children and adolescent which involves multiple organ system and is characterized by progressive clinical deterioration and ultimate development of severe immune dysfunction with opportunistic infections and secondary cancers resulting in a chronic and very complex illness. HIV infected infant and children now survive to adolescent and adulthood, and the challenges of providing HIV care are evolving into the challenges of providing both acute and chronic, lifelong care.